1982
DOI: 10.1136/bmj.285.6350.1233
|View full text |Cite
|
Sign up to set email alerts
|

Intensive attention improves glycaemic control in insulin-dependent diabetes without further advantage from home blood glucose monitoring: results of a controlled trial.

Abstract: Forty-six diabetics treated with twice-daily insulin were seen every two weeks for six months in an intensive education programme aided by regular home urine glucose testing. Control was improved with a decrease in 24-hour urinary glucose excretion (median 138 mmol/ 24 h (24-8 g/24 h) falling to 70 mmol/24 h (12-6 g/24 h); p <0 002), glycosylated haemoglobin concentration (mean 114± SD 2-3% falling to 10-4±1-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
64
1
6

Year Published

1990
1990
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(75 citation statements)
references
References 41 publications
4
64
1
6
Order By: Relevance
“…When this technique was introduced, it was assumed that patients who monitor their blood would achieve better control than those who tested their urine. Contrary to expectation, a controlled trial showed that patients randomized to blood or urine tests did equally well when equal time and attention was provided by their health care providers (14).…”
Section: Discussionmentioning
confidence: 66%
“…When this technique was introduced, it was assumed that patients who monitor their blood would achieve better control than those who tested their urine. Contrary to expectation, a controlled trial showed that patients randomized to blood or urine tests did equally well when equal time and attention was provided by their health care providers (14).…”
Section: Discussionmentioning
confidence: 66%
“…A capacidade da monitorização sangüínea em proporcionar melhores índices glicêmicos foi demonstrada em muitos estudos (10,12,14) Entretanto alguns trabalhos salientam que o bom controle metabólico é independente do tipo ou freqüência da monitorização domiciliar e que, ao longo do tempo, as melhoras obtidas nos níveis glicêmicos com qualquer tipo de monitorização, tendem a se deteriorar se não houver acompanhamento, atenção intensiva e envolvimento da equipe com os o pacientes (27,36,37,38) Estudos mais recentes salientam a necessidade de intensificação da monitorização sangüínea, de forma que o perfil glicêmico seja mais sensível as flutuações glicêmicas diárias e permita maior exatidão dos ajustes terapêuticos (14,17,20,29) Quando esta intensificação atinge o número de 4 vezes ao dia e os resultados são utilizados para o ajuste diário nas múltiplas doses de insulina o controle metabólico é seguramente otimizado (18,20) . A tentativa de melhorar o controle metabólico dos pacientes no nosso serviço por meio do incentivo à monitorização sangüínea 1 vez ao dia foi bem sucedida no momento anterior a este estudo.…”
Section: -Média Das Hba1c Antes E Após As Intervenções No Grupo a Sãunclassified
“…It seems likely that the initial improvement in HbA 1 observed in both groups following recruitment was due to the fact that participation in the study was suf®cient to motivate subjects to make the changes taught previously. The bene®cial effect of being in a study has been documented in other randomised studies (Korhonen et al, 1983;McCulloch et al, 1983;Worth et al, 1982).…”
Section: Discussionmentioning
confidence: 69%